On the evolutionary status of J stars - Muhel, Rohella (2008)
This research, which is an MSc diploma work in engineering physics at Luleå University of Technology, investigates the properties and possible origins of the J-type carbon stars. In particular, it shows that R stars are almost certainly progenitors of some, but not all, J stars. It also shows that the evolution of an intermediate mass AGB star can produce properties seen in J stars, albeit for a short time only. This research concludes that the J stars come from more than one kind of progenitor star, and that a full explanation is still lacking. This research was undertaken at Monash University in Melbourne (Australia) as part of the exchange programme between the two universities. Validerat; 20101217 (root)